Motivation and physical fitness in old people participating in a hydro-gymnastics - Farinha, Carlos (2018)
Introduction: The purpose of the present investigation was to evaluate the motivations and the impact of the hydro-gymnastics in the physical fitness of old people involved in a 16 weeks exercise program. Methods: Participants were 83 old people doing a community hydro-gymnastics exercise program. Motivations were assessed using the Sport Activity Motivation Questionnaire and physical fitness was evaluated using the Functional Fitness Test battery, in two separate moments with a 16 weeks interval. The assumption of normality was checked using the Kolmogorov-Smirnov test. Wilcoxon test was used to compare the group in different time moments. Results: Regarding motivations to hydro-gymnastics the items that scored higher were: “need to exercise”, “be with friends”, “make new friends” and “fun”. In terms of physical fitness variation, improvements in average were found in practically all fitness test between the 1st and 2nd evaluation, with significant statistical differences in 3 of the 5 tests applied. Conclusions: Old people´s major motives to participate in hydro-gymnastics are related to the motivational dimensions of physical fitness, general affiliation and pleasure. Additionally, hydro-gymnastics exercise programs have a positive impact to improve physical fitness in old people and play a determinant role on health promotion and successful aging.